Self-Efficacy, Self-Compassion, and Dietary Compliance Of Diabetes Mellitus Patients - Jek Amidos Pardede; Galvani Volta Simanjuntak; Marthalena Simamora; Melda Parapat (Akupun Tour Publisher, 2022)
Background: Diabetes Mellitus is a disease that cannot be cured, but it can be controlled so that patients can live their lives well. One of the ways to control this is by adjusting the diet. Purpose: The purpose of this study was to determine the relationship between self-efficacy and self-compassion with dietary compliance of diabetes mellitus patients. Method: The research method used was correlation analytic with a cross sectional approach. The population of this study is diabetes mellitus outpatients at RSUD Dolok Sanggul. Sample was taken by accidental technique of 50 people. Data collection using a questionnaire and data analysis using spearman correlation test with a significance level of 0.05. Result: The results showed that the majority of respondents had low self-efficacy as many as 33 people (66%), the majority of respondents had low self-compassion as many as 38 people(76%) and the majority of respondents diet compliance was low as many as 35 people (70%). The results of the Spearman correlation test between self-efficacy (p0,001; r 0,625) and self-compassion (p0.001 ; r 0,734) with dietary compliance of diabetes mellitus patients. Conclusion: There is a strong relationship between self-efficacy and self-compassion witt dietary compliance of diabetes mellitus patients. The better the self-efficacy and self-compassion, the more obedient the diabetic patient will be in implementing the diet program.